Women's Economic Empowerment through Islamic Social Finance: Integrating Waqf, Zakah, and Microfinance for Inclusive Development - Huma Khan; Adamu Abubakar Muhammad; Ahmad Babikir; Ismail Iliyasu Danladi; Muhammad Uba Babayo; Abdullah A. Afifi (Journal of Regional Development and Technology Initiatives, 2026)
Women economic empowerment has been at the heart of global discussions about development owing to the critical roles it plays in poverty alleviation, household welfare, inclusive economic development and growth. Nevertheless, an important proportion of women, especially in developing countries, still face poor access to financial services, productive assets and financial opportunities. Their entrepreneurship potentials continue to be untapped due to their poor access to capital. Limited financial resources and collateral requirements prevent poor women from accessing Conventional financing options. As part of the Islamic financial framework, zakah, waqf, sadaqa, and Islamic micro-financing are useful tools for social justice and promoting equal distribution of wealth. Hence this paper aims to present the Integrated Women Islamic Social Finance Empowerment Framework (IWISE) which is an effort to combine the elements of Islamic social finance with women empowerment entrepreneurship and capacity development into a single cohesive model. This study employs a qualitative research approach. The primary data collection consists of document analysis of Islamic classical legal texts, and reviews of current relevant literatures on Islamic social finance, women entrepreneurship, financial inclusion, micro financing and poverty alleviation. The study employs conceptual and analytical method to synthesis existing body of knowledge and put forward an integrate Islamic social finance for women’s economic development. Study shows that better integration of Zakah and Waqf Institutions, Islamic micro-financing institutions, governments and civil society could improve women access to finance, support the provision of business development, vocational skills, digital literacy, and other opportunities in the market place. Productive endowments (waqf) and zakat, could sustain entrepreneurial activities for women. This approach is expected to create synergistic and collaborative partnerships to advance women entrepreneurship, financially include women in the economy and sustainably enhance their livelihoods. This study adds to the existing body of literature on Islamic social finance through proposing a novel model of Integrated Women’s Islamic Social Finance Empowerment (IWISE) Frame work that strategically combine zakat, waqf and Islamic micro finance with capacity development and partnerships initiatives in the sphere of women entrepreneurship and economic development. This framework will provide a policy road map for policy makers, Islamic institutions and entrepreneurs for effective utilization of Islamic philanthropic and financial resources to ensure that Islamic social Finance become instruments of inclusive and sustainable human development through empowerments of women.